KOMPETENSI PROFESIONAL GURU DAN LINGKUNGAN BELAJAR TERHADAP MOTIVASI BELAJAR DI MASA PANDEMI COVID-19 - Lita Wulantika; Putri Sesah Nirmala Sari (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of teacher professional competence and learning environment on learning motivation during the Covid-19 pandemic. The method used in this study is an analytical approach, namely a quantitative approach and descriptive and verification methods. The samples used in this study were all students of class XII one of the Senior High Schools in the city of Bandung, so the number of samples used in this study were 123 samples. The analytical tools used in this study are multiple linear regression analysis, classical assumption testing, namely normality test, heteroscedasticity test, autocorrelation test, multicollinearity test, coefficient of determination analysis and hypothesis testing using the SPSS v25 a The results showed that the results of the T-Test of teachers' professional competence had a significant and significant effect on learning motivation, the learning environment had a significant and significant effect on learning motivation. In accordance with the results of the F test is a significant effect on learning motivation.